Effect of iodoacetic acid on the reproductive system of male mice - Liang, Yun; Huang, Xinshuang; Fang, Li; Wang, Mingjie; Yu, Chunxiao; Guan, Qingbo (Frontiers in Pharmacology, 2022)
Iodoacetic acid (IAA) is one of the most well-used water disinfection byproducts. Humans and animals are widely and continuously exposed to it. Many species of water disinfection byproducts are harmful to the reproductive system of organisms. Nevertheless, the potential impacts of IAA exposure on testosterone and spermatogenesis in vivo remain ambiguous. Spermatogenous cells are the site of spermatogenesis, Leydig cells are the site of testosterone synthesis, and Sertoli cells build the blood-testis barrier, providing a stable environment for the above important physiological functions. Therefore, we observed the effect of IAA on spermatogenic cells, Leydig cells and Sertoli cells in the testis. In this study, we found that oral administration of IAA (35 mg/kg body weight per day for 28 days) reduced sperm motility, affecting average path velocity and straight line velocity of sperm. In addition, IAA promoted the expression of γH2AX, a marker for DNA double-strand breaks. Moreover, IAA downregulated the protein expression of the scavenger receptor class B type 1 (SRB1), and decreased lipid droplet transport into Leydig cells, which reduced storage of testosterone synthesis raw materials and might cause a drop in testosterone production. Thus, our results indicated that IAA exposure affected spermatogenesis and testosterone synthesis by inducing DNA damage and reducing lipid droplet transport.